Association between circulating fibroblast growth factor 21, aerobic fitness, and aortic blood pressure in middle-aged and older women - Masahiro Matsui; Keisei Kosaki; Nobuhiko Akazawa; Koichiro Tanahashi; Makoto Kuro-o; Seiji Maeda (Japanese Society of Physical Fitness and Sports Medicine, 2019)
Circulating fibroblast growth factor-21 (FGF21) has been reported to correlate with development and progression of some chronic diseases including diabetes and obesity. However, the association between circulating FGF21 levels, aerobic fitness, and aortic blood pressure (BP) is still not fully understood. This study aimed to examine potential association between circulating FGF21 levels, aerobic fitness, and aortic BP in 118 middle-aged and older women. Aortic pulse pressure (PP) in the higher FGF21 group was significantly increased when compared to the lower FGF21 group (38.4 ± 1.1 vs. 34.9 ± 0.8 mmHg; P < 0.05). Multivariate analysis found the circulating FGF21 level to be an independent determinant of aortic PP (β = 0.169; P < 0.05); and this finding was also independently determined by VO2peak (β = −0.235; P < 0.01). Such a finding demonstrated that serum FGF21 levels were associated positively with aortic PP and negatively with aerobic fitness. These results have raised the possibility that FGF21 might contribute to an increase in aortic PP, and that the promotion of aerobic fitness might be effective in maintaining low FGF21 levels in middle-aged and older women.